Formulation optimization and characterization of colistin using sodium deoxycholate sulfate for intravenous administration - Bintang, Muhammad Ali Khumaini Mudhar (Prince of Songkla University, 2023)
Doctor of Philosophy (Pharmaceutical Sciences), 2023